Sensitivity analysis and uncertainty quantification of stiffness modulus using indirect tensile test - Mezouara, Hicham; Zniker, Houcine; Feddal, Ikram; El Kouifat, Mohammed Khalil; El Hasnaoui, Mohamed (Zielona Góra: Uniwersytet Zielonogórski)
The stiffness modulus is a critical element in pavement engineering, as its accurate measurement directly reflects the load-bearing capacity of the pavement section. Many researchers utilize indirect tensile tests in laboratory studies to determine this modulus. The pavement`s performance, as well as other properties of the pavement layers, can be directly influenced by this modulus.
Keywords: stiffness modulus; indirect tensile testing; uncertainty quantification; sensitivity analysis; asphalt mixtures